Co (at) ZrO2 composite material, preparation method thereof and application of Co (at) ZrO2 composite material in photocatalytic CO2 cycloaddition

Co@ZrO2 composite material was prepared by pyrolysis of UiO-66 template. Using multi-stage pore structure and electronic effects of bimetallic nanoparticles, the problem of insufficient activity of existing MOFs catalysts was solved, and efficient CO2 and epoxide cyclization was achieved. The reaction is improved, and the catalytic performance and photothermal conversion efficiency are improved.

CN119259049APending Publication Date: 2025-01-07ZHEJIANG SCI-TECH UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411260679.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing MOFs catalysts have insufficient catalytic activity in the cycloaddition reaction of low concentration CO2 and epoxide, and the large molecular structure of cobalt chloride hexahydrate leads to poor dispersion in the target product, affecting performance.

Method used

UiO-66 is used as a template for pyrolysis to prepare Co@ZrO2 composite materials. By constructing multi-stage pore MOFs, the plasmon resonance effect of bimetallic nanoparticles, Lewis acid and Lewis alkali active sites are used to achieve synergistic effect. High-efficiency photocatalyzed cycloaddition reaction between CO2 and epoxides.

Benefits of technology

Achieve high-efficiency photocatalytic cycloaddition reaction under low concentration CO2 conditions, improve the specific surface area and active sites of the catalyst, improve the photothermal conversion and catalytic performance, and significantly improve the cycloaddition of CO2 and epoxides. Reaction efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259049A_ABST
    Figure CN119259049A_ABST
Patent Text Reader

Abstract

The invention discloses a Co-coated ZrO2 composite material and a preparation method and application thereof in photocatalytic CO2 cycloaddition, and relates to the technical field of nano material preparation and application, and the preparation method comprises the following steps: adding a UiO-66 material and [Bmim] [CoCl3] into absolute methanol, and uniformly mixing to obtain a mixed solution; uniformly stirring and mixing the obtained mixed solution, and then performing rotary evaporation and drying to obtain a [Bmim] [CoCl3] coated UiO-66 material; and placing the obtained [Bmim] [CoCl3] coated UiO-66 in a hydrogen-argon mixed gas atmosphere for pyrolysis to obtain the Co coated ZrO2 composite material. The Co-coated ZrO2 composite material has the beneficial effects that the Co-coated ZrO2 composite material is prepared by directly pyrolyzing the [Bmim] [CoCl3]-coated UiO-66, and the Co-coated ZrO2 composite material has ultrahigh specific surface area and more active sites, can be used for carrying out cycloaddition reaction of CO2 and epoxide under the condition of light irradiation, and is high in energy conversion efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nano material preparation and application, and in particular to a Co@ZrO2 composite material and a preparation method thereof and application in photocatalytic CO2 cycloaddition. Background Art

[0002] Carbon dioxide (CO2), as one of the main greenhouse gases, has caused global warming, glacier melting, ocean acidification and other serious problems due to its rising content, which has aroused great concern from the international community. Carbon dioxide photocatalysis can collect greenhouse gases and directly convert them into high value-added chemicals without adsorption and storage. It can not only reduce CO2 emissions, but also reduce the consumption and dependence on non-renewable resources, promote a win-win situation of environmental benefits and economic growth, and has great development significance and practical needs.

[0003] MOFs are a new type of porous solid material composed of metal ions and organic ligands. They have highly controllable pore structures and surface chemical properties, which can achieve the storage and conversion of CO2 and help develop low-cost and high-efficiency CO2 capture technology. However, the internal structure of MOFs limits the reaction of metal active sites with gases, resulting in low catalytic activity. The low photocatalytic activity greatly limits its function, making it difficult to achieve efficient photocatalytic low-concentration CO2 and epoxide cycloaddition reactions.

[0004] For example, Liu et al. [Li Y, Weng S, Wang S, et al. Engineering the activity and stability of ZIF-8(Zn / Co)@g-C3N4 nanocomposites and their synergistic action in converting atmospheric CO2 into cyclic carbonates [J]. Journal of Colloid and Interface Science, 2024, 656: 24-34.] prepared a series of ZIF-8(Zn / Co)@g-C3N4 nanocomposites using a thermophysical composite strategy, which involves combining graphitic carbon nitride (g-C3N4) nanosheets with ZIF-8(Zn / Co). The abundant Lewis base sites in g-C3N4 are conducive to CO2 activation, and the abundant Lewis acid sites in ZIF-8(Zn / Co) can achieve effective epoxide activation. With the assistance of the co-catalyst TBAB, the yield of propylene carbonate catalyzed CO2 and propylene oxide was as high as 99%. The integration of g-C3N4 and ZIF-8 (Zn / Co) endows the catalytic material with excellent structural stability and significant catalytic activity, opening up a new path for efficient catalytic CO2 conversion.

[0005] Chinese patent CN115624976A discloses a preparation method and application of mosaic zirconium oxide / cobalt oxide composite nanoparticles, which is to mix UIO-66 with hexadecyltrimethylammonium bromide, cobalt chloride hexahydrate and 2-methylimidazole, and obtain UIO-66 / ZIF-67 through a secondary solvent thermal reaction; then calcine the obtained UIO-66 / ZIF-67 in air to obtain the mosaic ZrO2 / Co3O4 composite nanoparticles. Chinese patent CN108102111A discloses a cobalt ion doped metal organic framework material and a preparation method thereof, including mixing zirconium chloride, terephthalic acid, cobalt chloride hexahydrate and an organic solvent, stirring to obtain a precursor solution; and subjecting the precursor solution to a hydrothermal reaction to obtain a cobalt ion doped metal organic framework material. The above patents all use cobalt chloride hexahydrate. Since the molecular structure of cobalt chloride hexahydrate is relatively large and its dispersibility is relatively poor, it cannot be evenly dispersed in the target product, thereby affecting the performance of the product. Summary of the invention

[0006] In order to overcome at least one of the shortcomings and deficiencies of the above-mentioned prior art, the present invention aims to develop a method for preparing a Co@ZrO2 composite material by pyrolysis using UiO-66 as a template and its application in visible light catalytic CO2 cycloaddition. The present invention constructs a multi-level porous MOFs to encapsulate metal nanoparticles to achieve an efficient photocatalytic cycloaddition reaction under low concentration CO2 conditions. This type of catalyst utilizes the unique electronic effect of bimetallic nanoparticles, and by regulating the metal components therein, especially those metals with strong surface plasmon resonance effects, it has a wider absorption capacity in the visible light range. At the same time, MOFs (metal organic frameworks) provide a rich pore structure, which helps to enhance the enrichment of CO2 in the material. In addition, the Lewis acid active sites and halogen ions therein are conducive to the activation of CO2 and the ring-opening reaction of epoxides. Utilizing the plasma resonance effect of bimetallic nanoparticles, Lewis acid, Lewis base active sites and the multi-level pore structure of MOFs, this catalyst can work efficiently in synergy, thereby realizing the photocatalytic CO2 and epoxide cycloaddition reaction, which is used to prepare cyclic carbonates.

[0007] The technical solution of the present invention is as follows:

[0008] The first aspect of the present invention provides a method for preparing a Co@ZrO2 composite material, comprising the following steps:

[0009] The UiO-66 material and [Bmim][CoCl3] were added into anhydrous methanol and mixed evenly to obtain a mixed solution;

[0010] The obtained mixed solution was stirred and mixed evenly, and then rotary evaporated and dried to obtain [Bmim][CoCl3]@UiO-66 material;

[0011] The obtained [Bmim][CoCl3]@UiO-66 was pyrolyzed in a hydrogen-argon mixed gas atmosphere to obtain a Co@ZrO2 composite material.

[0012] Preferably, the preparation of the UiO-66 material comprises the following steps:

[0013] Add ZrOCl2·8H2O into the solvent and dissolve it by ultrasonic to obtain a metal salt solution;

[0014] Add terephthalic acid into a solvent and dissolve it by ultrasonication to obtain an organic ligand solution;

[0015] The obtained metal salt solution is mixed with the organic ligand solution, and then formic acid is added after mixing, and ultrasonic mixing is performed to mix uniformly. The mixture is stirred and reacted at 100-130° C. for a period of time. After cooling, the solid product is centrifuged, washed, and dried to obtain the UiO-66 material.

[0016] Preferably, in the preparation of the UiO-66 material, the molar concentration of ZrOCl2·8H2O in the metal salt solution is 0.5-1.0 mol / L, the molar concentration of terephthalic acid in the organic ligand solution is 0.5-1.5 mol / L, and the solvent is N,N-dimethylformamide.

[0017] Preferably, in the preparation of the UiO-66 material, the organic ligand and the metal salt are dissolved in formic acid by ultrasound, the ultrasound time is 5 to 30 minutes, and the stirring reaction time is 2 to 6 hours at 100 to 130°C.

[0018] Preferably, the preparation method of the [Bmim][CoCl3] comprises: mixing BmimCl and CoCl2·6H2O, heating and stirring, and drying after complete dissolution to obtain the [Bmim][CoCl3] ionic liquid.

[0019] Preferably, in the method for preparing [Bmim][CoCl3],

[0020] The molar ratio of BmimCl to CoCl2·6H2O is 0.8~1.2:0.8~1.2;

[0021] The heating temperature is 40 to 80°C and the stirring time is 1 to 3 hours;

[0022] The drying is vacuum drying, the vacuum drying temperature is 50-120° C., and the drying temperature is 10 h to 24 h.

[0023] Preferably, in the preparation of the Co@ZrO2 composite material, the mass ratio of the UiO-66 material to [Bmim][CoCl3] is 1:0.125-0.25, and the addition ratio of anhydrous methanol to UiO-66 material is 1-3 mL:20 mg.

[0024] Preferably, in the preparation of the Co@ZrO2 composite material, the temperature for stirring and mixing the mixed solution is 10 to 40°C and the time is 18 to 36 hours.

[0025] Preferably, in the preparation of the Co@ZrO2 composite material,

[0026] The rotary evaporation temperature is 30-50°C, and the rotary evaporation time is 1-2h;

[0027] The drying is vacuum drying, the vacuum drying temperature is 60-100° C., and the drying temperature is 12h-24h.

[0028] Preferably, in the preparation of the Co@ZrO2 composite material, the pyrolysis temperature is 400-700°C, and the pyrolysis time is 1-4 hours.

[0029] During the pyrolysis process of the composite material of the present invention, due to the high pyrolysis temperature, the ionic liquid is completely pyrolyzed, UiO-66 is completely decomposed, and the Co@ZrO2 composite material is obtained.

[0030] A second aspect of the present invention provides a Co@ZrO2 composite material, characterized in that it is prepared by the above-mentioned preparation method.

[0031] The third aspect of the present invention provides an application of the above-mentioned Co@ZrO2 composite material in the photocatalytic cycloaddition reaction of CO2 and epoxide at room temperature.

[0032] Preferably, the application method is: mixing the obtained Co@ZrO2 composite material with an epichlorohydrin solution, introducing CO2, and performing a cycloaddition reaction under light.

[0033] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0034] 1. The preparation method of the present invention is simple and quick to operate, green and environmentally friendly, and low in cost.

[0035] 2. The present invention prepares Co@ZrO2 composite material by direct pyrolysis of [Bmim][CoCl3]@UiO-66, which has ultra-high specific surface area and more active sites, can carry out CO2 and epoxide ring addition reaction under light irradiation conditions, and has high energy conversion efficiency; the Co@ZrO2 composite material obtained by the present invention has excellent photothermal conversion performance, can greatly improve the utilization efficiency of light and improve the catalytic performance.

[0036] 3. The Co@ZrO2 composite material prepared by the present invention has excellent catalytic performance in the photocatalytic CO2 and epoxide cycloaddition reaction, strong applicability, and good practical application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is the XRD pattern of the Co@ZrO2 composite material obtained in Example 3;

[0038] Figure 2 This is a performance diagram of the Co@ZrO2 composite material obtained in Example 3 in catalyzing the cycloaddition reaction of CO2 and epoxide under visible light. DETAILED DESCRIPTION

[0039] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0040] The present invention is further described in detail below with specific examples, but the present invention is not limited to the following specific examples.

[0041] Example 1

[0042] This embodiment prepares Co@ZrO2 composite material by direct pyrolysis of [Bmim][CoCl3]@UiO-66 and applies it in photocatalytic CO2 cycloaddition reaction, specifically including:

[0043] (1) ZrOCl2·8H2O (17 g) was added to N,N-dimethylformamide (100 mL) and dissolved by ultrasonic treatment for 15 min to obtain a metal salt solution A; terephthalic acid (8.3 g) was added to N,N-dimethylformamide (100 mL) and dissolved by ultrasonic treatment for 15 min to obtain an organic ligand solution B; the metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonic treatment for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain a UiO-66 material.

[0044] (2) 1.75 g of BmimCl and 2.38 g of CoCl2·6H2O were mixed, heated and stirred at 60°C for 2 h, and after complete dissolution, vacuum dried at 100°C for 15 h to obtain [Bmim][CoCl3] ionic liquid.

[0045] (3) Weigh the obtained UiO-66 material (200 mg) and [Bmim][CoCl3] (50 mg) and add them to anhydrous methanol (20 mL), mix them evenly by ultrasonication for 15 min, stir them at 25 °C for 24 h, rotary evaporate them at 60 °C for 1 h, and vacuum dry them for 12 h to obtain a composite material.

[0046] (4) Weigh [Bmim][CoCl3]@UiO-66 (100 mg) obtained in step (3), send it into a tubular furnace for pyrolysis in a hydrogen-argon mixed gas atmosphere at 600°C for 2 h, cool it to room temperature and take it out. The obtained 1#Co@ZrO2 material can be used directly.

[0047] (5) Weigh the 1#Co@ZrO2 composite material (15 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.

[0048] Example 2

[0049] This embodiment prepares Co@ZrO2 composite material by direct pyrolysis of [Bmim][CoCl3]@UiO-66 and applies it in photocatalytic CO2 cycloaddition reaction, specifically including:

[0050] (1) ZrOCl2·8H2O (17 g) was added to N,N-dimethylformamide (100 mL) and dissolved by ultrasonic treatment for 15 min to obtain a metal salt solution A; terephthalic acid (8.3 g) was added to N,N-dimethylformamide (100 mL) and dissolved by ultrasonic treatment for 15 min to obtain an organic ligand solution B; the metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonic treatment for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain a UiO-66 material.

[0051] (2) 1.75 g of BmimCl and 2.38 g of CoCl2·6H2O were mixed, heated and stirred at 60°C for 2 h, and after complete dissolution, vacuum dried at 100°C for 15 h to obtain [Bmim][CoCl3] ionic liquid.

[0052] (3) Weigh the obtained UiO-66 material (200 mg) and [Bmim][CoCl3] (25 mg), add them into anhydrous methanol (20 mL), mix them evenly by ultrasonication for 15 min, stir them at 25 ° C for 24 h, rotary evaporate them at 60 ° C for 1 h, and vacuum dry them for 12 h to obtain a composite material;

[0053] (4) Weigh [Bmim][CoCl3]@UiO-66 (100 mg) obtained in step (3), send it into a tubular furnace for pyrolysis in a hydrogen-argon mixed gas atmosphere at 600°C for 2 h, cool it to room temperature and take it out. The obtained 2#Co@ZrO2 material can be used directly.

[0054] (5) Weigh the 2#Co@ZrO2 composite material (15 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.

[0055] Example 3

[0056] This embodiment prepares Co@ZrO2 composite material by direct pyrolysis of [Bmim][CoCl3]@UiO-66 and applies it in photocatalytic CO2 cycloaddition reaction, specifically including:

[0057] (1) ZrOCl2·8H2O (17 g) was added to N,N-dimethylformamide (100 mL) and dissolved by ultrasonic treatment for 15 min to obtain a metal salt solution A; terephthalic acid (8.3 g) was added to N,N-dimethylformamide (100 mL) and dissolved by ultrasonic treatment for 15 min to obtain an organic ligand solution B; the metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonic treatment for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain a UiO-66 material.

[0058] (2) 1.75 g of BmimCl and 2.38 g of CoCl2·6H2O were mixed, heated and stirred at 60°C for 2 h, and after complete dissolution, vacuum dried at 100°C for 15 h to obtain [Bmim][CoCl3] ionic liquid.

[0059] (3) Weigh the obtained UiO-66 material (200 mg) and [Bmim][CoCl3] (30 mg) and add them to anhydrous methanol (20 mL) and mix them evenly by ultrasonication for 15 min, stir at 25 ° C for 24 h, rotary evaporate at 60 ° C for 1 h, and vacuum dry for 12 h to obtain a composite material;

[0060] (4) Weigh the [Bmim][CoCl3]@UiO-66 (100 mg) obtained in step (3), send it into a tubular furnace for pyrolysis in a hydrogen-argon mixed gas atmosphere at 600°C for 2 h, cool it to room temperature and then take it out. The obtained 3#Co@ZrO2 material can be used directly.

[0061] (5) Weigh the 3#Co@ZrO2 composite material (15 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.

[0062] Example 4

[0063] This embodiment prepares Co@ZrO2 composite material by direct pyrolysis of [Bmim][CoCl3]@UiO-66 and applies it in photocatalytic CO2 cycloaddition reaction, specifically including:

[0064] (1) ZrOCl2·8H2O (17 g) was added to N,N-dimethylformamide (100 mL) and dissolved by ultrasonic treatment for 15 min to obtain a metal salt solution A; terephthalic acid (8.3 g) was added to N,N-dimethylformamide (100 mL) and dissolved by ultrasonic treatment for 15 min to obtain an organic ligand solution B; the metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonic treatment for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain a UiO-66 material.

[0065] (2) 1.75 g of BmimCl and 2.38 g of CoCl2·6H2O were mixed, heated and stirred at 60°C for 2 h, and after complete dissolution, vacuum dried at 100°C for 15 h to obtain [Bmim][CoCl3] ionic liquid.

[0066] (3) Weigh the obtained UiO-66 material (200 mg) and [Bmim][CoCl3] (35 mg) and add them to anhydrous methanol (20 mL) and mix them evenly by ultrasonication for 15 min, stir at 25 ° C for 24 h, rotary evaporate at 60 ° C for 1 h, and vacuum dry for 12 h to obtain a composite material;

[0067] (4) Weigh the [Bmim][CoCl3]@UiO-66 (100 mg) obtained in step (3), send it into a tubular furnace for pyrolysis in a hydrogen-argon mixed gas atmosphere at 600°C for 2 h, cool it to room temperature and then take it out. The obtained 4#Co@ZrO2 material can be used directly.

[0068] (5) Weigh the 4#Co@ZrO2 composite material (15 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.

[0069] Example 5

[0070] This embodiment prepares Co@ZrO2 composite material by direct pyrolysis of [Bmim][CoCl3]@UiO-66 and applies it in photocatalytic CO2 cycloaddition reaction, specifically including:

[0071] (1) ZrOCl2·8H2O (17 g) was added to N,N-dimethylformamide (100 mL) and dissolved by ultrasonic treatment for 15 min to obtain a metal salt solution A; terephthalic acid (8.3 g) was added to N,N-dimethylformamide (100 mL) and dissolved by ultrasonic treatment for 15 min to obtain an organic ligand solution B; the metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonic treatment for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain a UiO-66 material.

[0072] (2) 1.75 g of BmimCl and 2.38 g of CoCl2·6H2O were mixed, heated and stirred at 60°C for 2 h, and after complete dissolution, vacuum dried at 100°C for 15 h to obtain [Bmim][CoCl3] ionic liquid.

[0073] (3) Weigh the obtained UiO-66 material (200 mg) and [Bmim][CoCl3] (40 mg) and add them to anhydrous methanol (20 mL) and mix them evenly by ultrasonication for 15 min, stir at 25 ° C for 24 h, rotary evaporate at 60 ° C for 1 h, and vacuum dry for 12 h to obtain a composite material;

[0074] (4) Weigh [Bmim][CoCl3]@UiO-66 (100 mg) obtained in step (3), send it into a tubular furnace for pyrolysis in a hydrogen-argon mixed gas atmosphere at 600°C for 2 h, cool it to room temperature and take it out. The obtained 5#Co@ZrO2 material can be used directly.

[0075] (5) Weigh the 5#Co@ZrO2 composite material (15 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.

[0076] Example 6

[0077] This embodiment prepares Co@ZrO2 composite material by direct pyrolysis of [Bmim][CoCl3]@UiO-66 and applies it in photocatalytic CO2 cycloaddition reaction, specifically including:

[0078] (1) ZrOCl2·8H2O (17 g) was added to N,N-dimethylformamide (100 mL) and dissolved by ultrasonic treatment for 15 min to obtain a metal salt solution A; terephthalic acid (8.3 g) was added to N,N-dimethylformamide (100 mL) and dissolved by ultrasonic treatment for 15 min to obtain an organic ligand solution B; the metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonic treatment for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain a UiO-66 material.

[0079] (2) 1.75 g of BmimCl and 2.38 g of CoCl2·6H2O were mixed, heated and stirred at 60°C for 2 h, and after complete dissolution, vacuum dried at 100°C for 15 h to obtain [Bmim][CoCl3] ionic liquid.

[0080] (3) Weigh the obtained UiO-66 material (200 mg) and [Bmim][CoCl3] (30 mg) and add them to anhydrous methanol (20 mL) and mix them evenly by ultrasonication for 15 min, stir at 25 ° C for 24 h, rotary evaporate at 60 ° C for 1 h, and vacuum dry for 12 h to obtain a composite material;

[0081] (4) Weigh the [Bmim][CoCl3]@UiO-66 (100 mg) obtained in step (3), send it into a tubular furnace for pyrolysis in a hydrogen-argon mixed gas atmosphere at 550°C for 2 h, cool it to room temperature and then take it out. The obtained 6#Co@ZrO2 material can be used directly.

[0082] (5) Weigh the 6#Co@ZrO2 composite material (15 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.

[0083] Example 7

[0084] This embodiment prepares Co@ZrO2 composite material by direct pyrolysis of [Bmim][CoCl3]@UiO-66 and applies it in photocatalytic CO2 cycloaddition reaction, specifically including:

[0085] (1) ZrOCl2·8H2O (17 g) was added to N,N-dimethylformamide (100 mL) and dissolved by ultrasonic treatment for 15 min to obtain a metal salt solution A; terephthalic acid (8.3 g) was added to N,N-dimethylformamide (100 mL) and dissolved by ultrasonic treatment for 15 min to obtain an organic ligand solution B; the metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonic treatment for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain a UiO-66 material.

[0086] (2) 1.75 g of BmimCl and 2.38 g of CoCl2·6H2O were mixed, heated and stirred at 60°C for 2 h, and after complete dissolution, vacuum dried at 100°C for 15 h to obtain [Bmim][CoCl3] ionic liquid.

[0087] (3) Weigh the obtained UiO-66 material (200 mg) and [Bmim][CoCl3] (30 mg) and add them to anhydrous methanol (20 mL) and mix them evenly by ultrasonication for 15 min, stir at 25 ° C for 24 h, rotary evaporate at 60 ° C for 1 h, and vacuum dry for 12 h to obtain a composite material;

[0088] (4) Weigh the [Bmim][CoCl3]@UiO-66 (100 mg) obtained in step (3), put it into a tubular furnace for pyrolysis in a hydrogen-argon mixed gas atmosphere at 500°C for 2 h, cool it to room temperature and take it out. The obtained 7#Co@ZrO2 material can be used directly.

[0089] (5) Weigh the 7#Co@ZrO2 composite material (15 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.

[0090] Example 8

[0091] This embodiment prepares Co@ZrO2 composite material by direct pyrolysis of [Bmim][CoCl3]@UiO-66 and applies it in photocatalytic CO2 cycloaddition reaction, specifically including:

[0092] (1) ZrOCl2·8H2O (17 g) was added to N,N-dimethylformamide (100 mL) and dissolved by ultrasonic treatment for 15 min to obtain a metal salt solution A; terephthalic acid (8.3 g) was added to N,N-dimethylformamide (100 mL) and dissolved by ultrasonic treatment for 15 min to obtain an organic ligand solution B; the metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonic treatment for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain a UiO-66 material.

[0093] (2) 1.75 g of BmimCl and 2.38 g of CoCl2·6H2O were mixed, heated and stirred at 60°C for 2 h, and after complete dissolution, vacuum dried at 100°C for 15 h to obtain [Bmim][CoCl3] ionic liquid.

[0094] (3) Weigh the obtained UiO-66 material (200 mg) and [Bmim][CoCl3] (30 mg) and add them to anhydrous methanol (20 mL) and mix them evenly by ultrasonication for 15 min, stir at 25 ° C for 24 h, rotary evaporate at 60 ° C for 1 h, and vacuum dry for 12 h to obtain a composite material;

[0095] (4) Weigh the [Bmim][CoCl3]@UiO-66 (100 mg) obtained in step (3), send it into a tubular furnace for pyrolysis in a hydrogen-argon mixed gas atmosphere at 700°C for 2 h, cool it to room temperature and take it out. The obtained 8#Co@ZrO2 material can be used directly.

[0096] (5) Weigh the 8#Co@ZrO2 composite material (15 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.

[0097] The powder diffraction results of the Co@ZrO2 composite material obtained in Example 3 are as follows: Figure 1 As shown, the sample shows the characteristic peak of Co phase. The characteristic peak of Co phase is weak, indicating that the Co content in the composite material prepared by the present invention is low or the size is small. Example 3 Preparation of Co@ZrO2 composite material by direct pyrolysis of [Bmim][CoCl3]@UiO-66 and application in photocatalytic CO2 cycloaddition reaction: The performance test results of the material in catalyzing CO2 and epoxide cycloaddition reaction under visible light are shown in Figure 2The results show that the reaction performance of the material obtained by pyrolysis at a suitable temperature is significantly enhanced, and a conversion rate of 97% and a selectivity of 99% can be achieved within 6 hours, indicating that the Co@ZrO2 composite material can greatly improve the utilization efficiency of light and improve the catalytic performance.

[0098] Comparative Example 1 ([Bmim][CoCl3] is not added in step 3)

[0099] This comparative example provides a method for preparing UiO-66-600 material, comprising the following steps:

[0100] (1) Add ZrOCl2·8H2O (17 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain a metal salt solution A; add terephthalic acid (8.3 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain an organic ligand solution B;

[0101] (2) The metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonication for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain UiO-66 material;

[0102] (3) Weigh the UiO-66 material (100 mg) obtained in step (2), put it into a tubular furnace for pyrolysis in a hydrogen-argon mixed atmosphere at 600° C. for 2 h, cool it to room temperature and take it out to obtain the UiO-66-600 material which can be used directly.

[0103] (4) Weigh the UiO-66-600 composite material (15 mg) obtained in step (3), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.

[0104] Comparative Example 2 (CoCl2·6H2O was used instead of [Bmim][CoCl3] in step 3)

[0105] This comparative example provides a method for preparing a Co / ZrO2 material, comprising the following steps:

[0106] (1) Add ZrOCl2·8H2O (17 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain a metal salt solution A; add terephthalic acid (8.3 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain an organic ligand solution B;

[0107] (2) The metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonication for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain UiO-66 material;

[0108] (3) Weigh the UiO-66 material (200 mg) obtained in step (2) and CoCl2·6H2O (30 mg), add them to anhydrous methanol (20 mL), mix them evenly by ultrasonication for 15 min, stir them at 25 ° C for 24 h, rotary evaporate them at 60 ° C for 1 h, and vacuum dry them for 12 h to obtain a composite material;

[0109] (4) Weigh the CoCl2·6H2O / UiO-66 (100 mg) obtained in step (3), put it into a tubular furnace for pyrolysis in a hydrogen-argon mixed atmosphere at 600°C for 2 h, cool it to room temperature and take it out to obtain UiO-66-600 material which can be used directly.

[0110] (5) Weigh the UiO-66-600 composite material (15 mg) obtained in step (3), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.

[0111] Comparative Example 3 (pyrolysis temperature in step 4 is 300°C)

[0112] This comparative example provides a method for preparing Co@ZrO2 material, comprising the following steps:

[0113] (1) Add ZrOCl2·8H2O (17 g) to N,N-dimethylformamide (100 mL), and dissolve it by ultrasonic treatment for 15 min to obtain a metal salt solution A; add terephthalic acid (8.3 g) to N,N-dimethylformamide (100 mL), and dissolve it by ultrasonic treatment for 15 min to obtain an organic ligand solution B; mix the metal salt solution A obtained in step (1) with the organic ligand solution B, add formic acid (100 mL) after mixing, and mix them by ultrasonic treatment for 15 min, stir and react at 120° C. for 4 h, cool and centrifuge, wash with N,N-dimethylformamide and anhydrous methanol respectively, and dry in vacuo at 80° C. for 24 h to obtain a UiO-66 material;

[0114] (2) 1.75 g of BmimCl and 2.38 g of CoCl2·6H2O were mixed, heated and stirred at 60°C for 2 h, and after complete dissolution, vacuum dried at 100°C for 15 h to obtain [Bmim][CoCl3] ionic liquid.

[0115] (3) Weigh the obtained UiO-66 material (200 mg) and [Bmim][CoCl3] (30 mg) and add them to anhydrous methanol (20 mL) and mix them evenly by ultrasonication for 15 min, stir at 25 ° C for 24 h, rotary evaporate at 60 ° C for 1 h, and vacuum dry for 12 h to obtain a composite material;

[0116] (4) Weigh the [Bmim][CoCl3]@UiO-66 (100 mg) obtained in step (3), send it into a tubular furnace for pyrolysis in a hydrogen-argon mixed gas atmosphere at 300°C for 2 h, cool it to room temperature and then take it out. The obtained Co@ZrO2 material can be used directly.

[0117] (5) Weigh the Co@ZrO2 composite material (15 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.

[0118] Comparative Example 4 (pyrolysis temperature in step 4 is 800°C)

[0119] This comparative example provides a method for preparing Co@ZrO2 material, comprising the following steps:

[0120] (1) Add ZrOCl2·8H2O (17 g) to N,N-dimethylformamide (100 mL), and dissolve it by ultrasonic treatment for 15 min to obtain a metal salt solution A; add terephthalic acid (8.3 g) to N,N-dimethylformamide (100 mL), and dissolve it by ultrasonic treatment for 15 min to obtain an organic ligand solution B; mix the metal salt solution A obtained in step (1) with the organic ligand solution B, add formic acid (100 mL) after mixing, and mix them by ultrasonic treatment for 15 min, stir and react at 120° C. for 4 h, cool and centrifuge, wash with N,N-dimethylformamide and anhydrous methanol respectively, and dry in vacuo at 80° C. for 24 h to obtain a UiO-66 material;

[0121] (2) 1.75 g of BmimCl and 2.38 g of CoCl2·6H2O were mixed, heated and stirred at 60°C for 2 h, and after complete dissolution, vacuum dried at 100°C for 15 h to obtain [Bmim][CoCl3] ionic liquid.

[0122] (3) Weigh the UiO-66 material (200 mg) obtained in step (2) and [Bmim][CoCl3] (30 mg), add them to anhydrous methanol (20 mL), mix them evenly by ultrasonication for 15 min, stir at 25 ° C for 24 h, rotary evaporate at 60 ° C for 1 h, and vacuum dry for 12 h to obtain a composite material;

[0123] (4) Weigh the [Bmim][CoCl3]@UiO-66 (100 mg) obtained in step (3), put it into a tubular furnace for pyrolysis in a hydrogen-argon mixed gas atmosphere at 800°C for 2 h, cool it to room temperature and take it out. The obtained Co@ZrO2 material can be used directly.

[0124] (5) Weigh the Co@ZrO2 composite material (15 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.

[0125] Comparative Example 5 (the mass ratio of UiO-66 material to [Bmim][CoCl3] was changed to 1:0.1)

[0126] This comparative example provides a method for preparing Co@ZrO2 material, comprising the following steps:

[0127] (1) Add ZrOCl2·8H2O (17 g) to N,N-dimethylformamide (100 mL), and dissolve it by ultrasonic treatment for 15 min to obtain a metal salt solution A; add terephthalic acid (8.3 g) to N,N-dimethylformamide (100 mL), and dissolve it by ultrasonic treatment for 15 min to obtain an organic ligand solution B; mix the metal salt solution A obtained in step (1) with the organic ligand solution B, add formic acid (100 mL) after mixing, and mix them by ultrasonic treatment for 15 min, stir and react at 120° C. for 4 h, cool and centrifuge, wash with N,N-dimethylformamide and anhydrous methanol respectively, and dry in vacuo at 80° C. for 24 h to obtain a UiO-66 material;

[0128] (2) 1.75 g of BmimCl and 2.38 g of CoCl2·6H2O were mixed, heated and stirred at 60°C for 2 h, and after complete dissolution, vacuum dried at 100°C for 15 h to obtain [Bmim][CoCl3] ionic liquid.

[0129] (3) Weigh the UiO-66 material (200 mg) obtained in step (2) and [Bmim][CoCl3] (20 mg), add them to anhydrous methanol (20 mL), mix them by ultrasonication for 15 min, stir them at 25 ° C for 24 h, rotary evaporate them at 60 ° C for 1 h, and vacuum dry them for 12 h to obtain a composite material;

[0130] (4) Weigh [Bmim][CoCl3]@UiO-66 (100 mg) obtained in step (3), send it into a tubular furnace for pyrolysis in a hydrogen-argon mixed gas atmosphere at 600°C for 2 h, cool it to room temperature and then take it out. The obtained Co@ZrO2 material can be used directly.

[0131] (5) Weigh the Co@ZrO2 composite material (15 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.

[0132] Comparative Example 6 (the mass ratio of UiO-66 material to [Bmim][CoCl3] was changed to 1:0.3)

[0133] This comparative example provides a method for preparing Co@ZrO2 material, comprising the following steps:

[0134] (1) Add ZrOCl2·8H2O (17 g) to N,N-dimethylformamide (100 mL), and dissolve it by ultrasonic treatment for 15 min to obtain a metal salt solution A; add terephthalic acid (8.3 g) to N,N-dimethylformamide (100 mL), and dissolve it by ultrasonic treatment for 15 min to obtain an organic ligand solution B; mix the metal salt solution A obtained in step (1) with the organic ligand solution B, add formic acid (100 mL) after mixing, and mix them by ultrasonic treatment for 15 min, stir and react at 120° C. for 4 h, cool and centrifuge, wash with N,N-dimethylformamide and anhydrous methanol respectively, and dry in vacuo at 80° C. for 24 h to obtain a UiO-66 material;

[0135] (2) 1.75 g of BmimCl and 2.38 g of CoCl2·6H2O were mixed, heated and stirred at 60°C for 2 h, and after complete dissolution, vacuum dried at 100°C for 15 h to obtain [Bmim][CoCl3] ionic liquid.

[0136] (3) Weigh the UiO-66 material (200 mg) obtained in step (2) and [Bmim][CoCl3] (60 mg), add them to anhydrous methanol (20 mL), mix them evenly by ultrasonication for 15 min, stir them at 25 ° C for 24 h, rotary evaporate them at 60 ° C for 1 h, and vacuum dry them for 12 h to obtain a composite material;

[0137] (4) Weigh the [Bmim][CoCl3]@UiO-66 (100 mg) obtained in step (3), put it into a tubular furnace for pyrolysis in a hydrogen-argon mixed gas atmosphere at 600°C for 2 h, cool it to room temperature and take it out. The obtained Co@ZrO2 material can be used directly.

[0138] (5) Weigh the Co@ZrO2 composite material (15 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.

[0139] The following tests were performed on the Co@ZrO2 materials and UiO-66-600 materials obtained in Examples 1 to 8 and Comparative Examples 1 to 6:

[0140] (1) The powder diffraction (XRD) results of the 3#Co@ZrO2 material obtained in Example 3 are as follows: Figure 1 As shown, the characteristic peaks of ZrO2 and Co in 3#Co@ZrO2 material are consistent with the standard card, indicating that Co is successfully loaded on ZrO2 to synthesize Co@ZrO2 material.

[0141] (2) Example 3 Co@ZrO2 material was prepared by direct pyrolysis of [Bmim][CoCl3]@UiO-66 composite and applied in photocatalytic CO2 cycloaddition reaction. The performance test results of the material for catalytic CO2 and epoxide cycloaddition reaction under visible light are as follows: Figure 2 As shown, the results show that the reaction performance of the material obtained by pyrolysis at a suitable temperature is significantly enhanced, and a conversion rate of 97% and a selectivity of 99% can be achieved within 6 hours, indicating that Co@ZrO2 material can greatly improve the utilization efficiency of light and improve catalytic performance.

[0142] (3) The materials of Examples 1 to 8 and Comparative Examples 1 to 6 were used to catalyze the cycloaddition reaction of CO2 and epichlorohydrin to prepare propylene carbonate. The results are listed in Table 1.

[0143] Table 1

[0144] sample Conversion rate Selectivity <![CDATA[1#Co@ZrO2]]> 74% 99% <![CDATA[2#Co@ZrO2]]> 75% 99% <![CDATA[3#Co@ZrO2]]> 97% 99% <![CDATA[4#Co@ZrO2]]> 80% 99% <![CDATA[5#Co@ZrO2]]> 89% 99% <![CDATA[6#Co@ZrO2]]> 85% 99% <![CDATA[7#Co@ZrO2]]> 80% 99% <![CDATA[8#Co@ZrO2]]> 90% 99% Comparative Example 1 65% 99% Comparative Example 2 66% 99% Comparative Example 3 67% 99% Comparative Example 4 69% 99% Comparative Example 5 66% 99% Comparative Example 6 71% 99%

[0145] It can be seen from Table 1 that the conversion rate of Co@ZrO2 prepared in Examples 1 to 8 is above 74%, and the selectivity is 99%. Therefore, the Co@ZrO2 composite material prepared by the present invention through direct pyrolysis of [Bmim][CoCl3]@UiO-66 has an ultra-high specific surface area and more active sites, can carry out CO2 and epoxide ring addition reaction under light irradiation conditions, and has high energy conversion efficiency.

[0146] In Comparative Example 1, [Bmim][CoCl3] was not added to form a composite material with UiO-66. Instead, UiO-66-600 material was prepared using UiO-66 as a raw material. The conversion rate was only 65%, which was significantly lower than that of Examples 1 to 8.

[0147] The CoCl2·6H2O / UiO-66 material prepared in Comparative Example 2 catalyzes the cycloaddition reaction of CO2 and epoxide under the same conditions as the 3#Co@ZrO2 material prepared in Example 3, and the conversion rate is 66%, which is much lower than that in Example 3.

[0148] The Co@ZrO2 material prepared in Comparative Example 3 catalyzes the cycloaddition reaction of CO2 and epoxide under the same conditions as the 3#Co@ZrO2 material prepared in Example 3, and the conversion rate is 67%, which is much lower than that in Example 3.

[0149] The Co@ZrO2 material prepared in Comparative Example 4 catalyzes the cycloaddition reaction of CO2 and epoxide under the same conditions as the Co@ZrO2 material prepared in Example 3, and the conversion rate is 69%, which is much lower than that in Example 3.

[0150] The Co@ZrO2 material prepared in Comparative Example 5 catalyzes the cycloaddition reaction of CO2 and epoxide under the same conditions as the Co@ZrO2 material prepared in Example 3, and the conversion rate is 66%, which is much lower than that in Example 3.

[0151] The Co@ZrO2 material prepared in Comparative Example 6 catalyzes the cycloaddition reaction of CO2 and epoxide under the same conditions as the Co@ZrO2 material prepared in Example 3, and the conversion rate is 71%, which is much lower than that in Example 3.

[0152] Therefore, by comparing the catalytic performance results of the above comparative example with those of Example 3, it is found that the Co@ZrO2 composite material obtained by direct pyrolysis of [Bmim][CoCl3]@UiO-66 in Example 3 has excellent performance in catalyzing the cycloaddition reaction of CO2 and epoxide under light. Therefore, the addition of [Bmim][CoCl3] is beneficial to improving the catalytic performance of the material. When the reaction temperature increases within a certain range, the conversion rate increases; similarly, as the amount of catalyst increases, the conversion rate also increases. However, if it exceeds a certain range, the conversion rate will decrease.

[0153] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a Co@ZrO2 composite material, characterized in that: The following steps are involved: The UiO-66 material and [Bmim][CoCl3] were added into anhydrous methanol and mixed evenly to obtain a mixed solution; The obtained mixed solution was stirred and mixed evenly, and then rotary evaporated and dried to obtain [Bmim][CoCl3]@UiO-66 material; The obtained [Bmim][CoCl3]@UiO-66 was pyrolyzed in a hydrogen-argon mixed gas atmosphere to obtain a Co@ZrO2 composite material.

2. The method for preparing a Co@ZrO2 composite material according to claim 1, characterized in that: The preparation method of the UiO-66 material comprises the following steps: Add ZrOCl2·8H2O into the solvent and dissolve it by ultrasonic to obtain a metal salt solution; Adding terephthalic acid into a solvent and dissolving it by ultrasonication to obtain an organic ligand solution; The obtained metal salt solution is mixed with the organic ligand solution, and then formic acid is added after mixing, and ultrasonic mixing is performed to mix uniformly. The mixture is stirred and reacted at 100-130° C. for a period of time. After cooling, the solid product is centrifuged, washed, and dried to obtain the UiO-66 material.

3. The method for preparing a Co@ZrO2 composite material according to claim 2, characterized in that: In the preparation of the UiO-66 material, the molar concentration of ZrOCl2·8H2O in the metal salt solution is 0.5-1.0 mol / L, the molar concentration of terephthalic acid in the organic ligand solution is 0.5-1.5 mol / L, and the solvent is N,N-dimethylformamide.

4. The method for preparing a Co@ZrO2 composite material according to claim 2, characterized in that: In the preparation of the UiO-66 material, the organic ligand and the metal salt are dissolved in formic acid by ultrasound, the ultrasound time is 5 to 30 minutes, and the stirring reaction time is 2 to 6 hours at 100 to 130°C.

5. The method for preparing a Co@ZrO2 composite material according to claim 1, characterized in that: The preparation method of [Bmim][CoCl3] comprises: mixing BmimCl and CoCl2·6H2O, heating and stirring, and drying after the mixture is completely dissolved to obtain [Bmim][CoCl3] ionic liquid.

6. The method for preparing a Co@ZrO2 composite material according to claim 5, characterized in that: In the preparation method of [Bmim][CoCl3], The molar ratio of BmimCl to CoCl2·6H2O is 0.8~1.2:0.8~1.2; The heating temperature is 40 to 80°C and the stirring time is 1 to 3 hours; The drying is vacuum drying, the vacuum drying temperature is 50-120° C., and the drying temperature is 10 h to 24 h.

7. The method for preparing a Co@ZrO2 composite material according to claim 1, characterized in that: In the preparation of the Co@ZrO2 composite material, the mass ratio of the UiO-66 material to [Bmim][CoCl3] is 1:0.125-0.25, and the addition ratio of anhydrous methanol to the UiO-66 material is 1-3 mL:20 mg.

8. The method for preparing a Co@ZrO2 composite material according to claim 1, characterized in that: In the preparation of the Co@ZrO2 composite material, The mixed solution is stirred at a temperature of 10 to 40° C. for 18 to 36 hours; The rotary evaporation temperature is 30-50°C, and the rotary evaporation time is 1-2h; The drying is vacuum drying, the vacuum drying temperature is 60-100°C, and the drying temperature is 12h-24h; The pyrolysis temperature is 400-700° C., and the pyrolysis time is 1-4 hours.

9. A Co@ZrO2 composite material, characterized in that: The method is prepared according to any one of claims 1 to 8.

10. Use of the Co@ZrO2 composite material as claimed in claim 9 in the photocatalytic cycloaddition reaction of CO2 and epoxide at room temperature.

Citation Information

Patent Citations

  • MOFs derived three-dimensional hierarchical pore Co / NC composite material and preparation method thereof

    CN112495416A

  • CN (at) ZrO2 composite material and application thereof in catalysis of cycloaddition reaction of CO2 and epoxide

    CN114939431A

  • Preparation method of IL (at) MOF composite material and application of IL (at) MOF composite material in gas adsorption separation

    CN115350689A

  • Ionic liquid encapsulated metal organic framework based thin film nanocomposite membrane for metal IONS separation

    WO2023247987A1